Konsep Dakwah Islam terhadap Pluralitas Agama dalam Tafsir Al-Misbah Karya M. Quraish Shihab - Abdul Wahab; Kholifatus Sa'adah (An-Nida : Jurnal Komunikasi Islam, 2015)
This article is the result of research that first goal, to know about the concept of propaganda of religious plurality. Secondly, to reveal the concept of propaganda of religious plurality by M. Quraish Sihab in Tafsir Al-Misbah. This type of research is the Research Library with a thematic approach. The last few years the issue of religious plurality a trending topic that is debated by the scholars, even for the clergy. This has encouraged M. Quraish Shihab to reveal to all mankind, especially Muslims through tafsir al-Misbah who argued that the Qur'an has been preached about the importance of mutual respect, respect and tolerance among religions. M. Quraish Shihab stated the three concepts of propaganda, namely: the concept of truth and religious purity, safety concept, and the concept of tolerance. Of the three concepts can be concluded that Islam is a religion that contains the truth and the true purity must be preached to the whole human race to support their safety and happiness. But if they reject this call, then be tolerant and inclusive is a wise choice, to give them to the decision of Allah SWT.